2020
DOI: 10.1186/s12916-020-01687-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influenza vaccination in Kenya: an economic evaluation using dynamic transmission modelling

Abstract: Background: There is substantial burden of seasonal influenza in Kenya, which led the government to consider introducing a national influenza vaccination programme. Given the cost implications of a nationwide programme, local economic evaluation data are needed to inform policy on the design and benefits of influenza vaccination. We set out to estimate the cost-effectiveness of seasonal influenza vaccination in Kenya. Methods: We fitted an age-stratified dynamic transmission model to active surveillance data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(49 citation statements)
references
References 51 publications
0
49
0
Order By: Relevance
“…More specific data on actual changes in utilisation and prices was asked if this was available; however, this did not include asking the pharmacists to break down changes in utilisation patterns and prices per month as this was deemed too problematic for this initial study. In addition, it was envisaged there would be limited impact of seasonality in view of year-round influenza activity in some African countries and no real pattern in others ( WHO, 2012 ; Dawa et al, 2020 ; WHO Regional Office for Africa, 2020 ) although research is ongoing in this area to address current knowledge gaps ( Sambala et al, 2018 ). In addition, generally limited use of hydroxychloroquine in immunological diseases such as rheumatoid arthritis with concerns over its effectiveness compared with other disease modifying therapies ( Rempenault et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…More specific data on actual changes in utilisation and prices was asked if this was available; however, this did not include asking the pharmacists to break down changes in utilisation patterns and prices per month as this was deemed too problematic for this initial study. In addition, it was envisaged there would be limited impact of seasonality in view of year-round influenza activity in some African countries and no real pattern in others ( WHO, 2012 ; Dawa et al, 2020 ; WHO Regional Office for Africa, 2020 ) although research is ongoing in this area to address current knowledge gaps ( Sambala et al, 2018 ). In addition, generally limited use of hydroxychloroquine in immunological diseases such as rheumatoid arthritis with concerns over its effectiveness compared with other disease modifying therapies ( Rempenault et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our analyses demonstrate the importance of assumed cost-effectiveness thresholds when determining whether health interventions are cost-effective or not. Kenya does not have an official cost-effectiveness threshold, but Dawa et al (2020) reported that vaccination with current seasonal influenza vaccines in Kenya had a low probability of being cost-effective given WTP thresholds of 1-51% of per capita GDP. To address uncertainty around thresholds, we used a wide range of values ranging from extremely low WHO "best buys" threshold reserved for evaluating some of the most cost-effective programmes that WHO has ever evaluated (21), to very high 1-3 times GDP per capita thresholds representing the potential value of human capital associated with disability (24).…”
Section: Discussionmentioning
confidence: 99%
“…A key strength of our epidemiological model is the direct incorporation of vaccine-derived immunity waning over multiple years, with ageing of the population, which is required to evaluate next generation vaccines with benefits that last several years. This contrasts to many seasonal vaccination models where vaccine-derived immunity is not tracked across seasons (2,13). In contrast with the marked annual seasonality of influenza in temperate regions (27), influenza epidemics in Kenya do not have a regular seasonal pattern, with substantial transmission in between epidemics, which we included by separately modelling the inter-epidemic periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations